Konsep Terms Of Trade dan Dampaknya Terhadap Ekonomi Suatu Negara - Arinda Ramadani; Yuyun Eva Elviana; Mohammad Khafid Mudlofar; Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Terms of Trade (ToT) is a crucial indicator in international trade that illustrates the ratio between a country's export prices and import prices. This concept provides an overview of a country's purchasing power in the global market and reflects the relative benefits gained from trade. An increase in ToT indicates enhanced purchasing power, leading to benefits such as trade surpluses, strengthened currency value, and economic growth. Conversely, a decline in ToT negatively impacts a country, causing inflation, trade deficits, and weakened public purchasing power. Factors such as global commodity price fluctuations, exchange rates, export-import demand, and trade policies significantly influence ToT. This study highlights the importance of understanding ToT as a strategic tool in formulating trade and economic policies, especially for countries reliant on commodity exports. With proper understanding, countries can mitigate the adverse effects of ToT fluctuations and enhance societal welfare through adaptive and responsive policies.